Physiological and biomechanical in different swimming intensities - Sebastião Iberes Lopes de Melo; Oscar Amauri Erichsen; Roberta Gabriela Oliveira Gatti (Universidade Federal de Santa Catarina, 2004)
The objective of this study was to analyze the physiological and biomechanical responses of swimmers at different swimming intensities. The intentionally selected sample was composed by seven athletes with swimming times for qualifying on the Brazilian Swimming Championship. A series of 8x200 free style swimming at speeds of 80%, 85%, 90%, 95% and 100% of individual maximum effort was used as the task. A film camera of 60 Hz and an Accusport mMol lactimeter were used for data collection. Descriptive statistics, analysis of variance (ANOVA) with "post-hoc" Tukey test and Spearman's correlation were used for statistical analyses to identify the differences between athletes for the variables blood lactate, crawl stroke frequency (FB) and dimension (BR) at different intensities. The level of significance was set at 0.05. Based on the results, there were significant differences on swimming technique among effort intensities, for both the physiological and mechanical responses, especially at levels above 95% individual maximum effort. The high correlation between blood lactate and crawl stroke frequency and length, and between crawl stroke frequency and length, with the last two correlations being negative, indicated that the proposed series was adequate to analyze physiological and biomechanical response. It was concluded that as the intensity increases, there is a need for mechanical adjustments to enable the athletes to endure different speeds. It was also possible to establish the ideal swimming speed for each energetic zone, providing data for coaches and athletes to train both speed and technique within the specific energetic zones. RESUMO O objetivo deste estudo foi analisar as respostas fisiológicas e biomecânicas de nadadores em diferentes intensidades de nado. A amostra, intencionalmente escolhida, foi composta por sete atletas que possuíam índices de participação em campeonato brasileiro absoluto. Foi utilizada como tarefa de estudo uma série de 8x200 metros nado livre com velocidades de 80%, 85%, 90%, 95% e 100% do percentual de esforço de cada nadador. Como instrumento utilizou-se uma filmadora 60Hz e um lactímetro da Accusport mMol. No tratamento estatístico fez-se uso da estatística descritiva, análise de variância (ANOVA), "post-hoc" Tukey e correlação de Spearman, todos com nível de significância de 95%. Buscou-se com a análise estatística identificar as diferenças entre os atletas para as variáveis lactato sanguíneo, frequência de braçada (FB) e dimensão de braçada (BR) nas diferentes intensidades. A partir dos resultados pode-se constatar que os atletas apresentaram diferenças estatisticamente significantes entre as intensidades de esforço, tanto nas respostas fisiológica quanto na biomecânica da técnica de nado, situação observada, principalmente, em níveis acima de 95% de esforço. Constatou-se também alta correlação entre as variáveis lactato com freqüência de braçada, e com o comprimento da braçada, e da freqüência de braçada com o comprimento de braçada, sendo as duas últimas inversas, indicando que a série utilizada foi adequada para analisar respostas fisiológica e biomecânica em nadadores. Os resultados possibilitaram concluir que com o aumento da intensidade há necessidade de ajustes mecânicos para que os atletas possam suportar diferentes velocidades. Também foi possível estabelecer a velocidade de nado ideal para cada zona energética, fornecendo subsídios para técnicos e atletas treinarem as variáveis velocidade e técnica de nado dentro das zonas energéticas específicas.